Roles of Diacylglycerols and Ceramides in Hepatic Insulin Resistance. (July 2017) - Petersen, Max C.; Shulman, Gerald I.
Abstract : Although ample evidence links hepatic lipid accumulation with hepatic insulin resistance, the mechanistic basis of this association is incompletely understood and controversial. Diacylglycerols (DAGs) and ceramides have emerged as the two best-studied putative mediators of lipid-induced hepatic insulin resistance. Both lipids were first associated with insulin resistance in skeletal muscle and were subsequently hypothesized to mediate insulin resistance in the liver. However, the putative roles for DAGs and ceramides in hepatic insulin resistance have proved more complex than originally imagined, with various genetic and pharmacologic manipulations yielding a vast and occasionally contradictory trove of data to sort. In this review we examine the state of this field, turning a critical eye toward both DAGs and ceramides as putative mediators of lipid-induced hepatic insulin resistance. Trends: Nonalcoholic fatty liver disease is the most common liver disease in industrialized nations and is strongly associated with hepatic insulin resistance, a key driver of type 2 diabetes. Although stored hepatic triglyceride is not thought to directly impair insulin action, two lipid classes proposed to mediate lipid-induced hepatic insulin resistance are ceramides and diacylglycerols (DAGs). A causal role for DAGs in hepatic insulin resistance is supported by human correlative studies and a direct pathophysiologic mechanism in rodents but challenged by a few rodent models with increased hepatic DAG but preserved hepatic insulin sensitivity. A causal role for ceramides in hepatic insulin resistance is supported by several rodent models in which decreasing ceramides improves hepatic insulin action but challenged by an inconsistent relationship between hepatic ceramide content and hepatic insulin resistance.